Disrupting dorsolateral prefrontal cortex by rTMS reduces the P300 based marker of deception. Issue 4 (3rd March 2017) - Karton, Inga; Bachmann, Talis
Abstract: Objective: Quite many studies have revealed certain brain‐process signatures indicative of subject's deceptive behavior. These signatures are neural correlates of deception. However, much less is known about whether these signatures can be modified by noninvasive brain stimulation techniques representing methods of causal intervention of brain processes and the corresponding behavior. Our purpose was to explore whether such methods have an effect on these signatures. Methods: It is well known that electroencephalographic event‐related potential component, P300, is sensitive to perception of critical items in a concealed information test, one of the central methods in deception studies. We examined whether the relative level of expression of P300 as a neural marker of deception can be manipulated by means of noninvasive neuromodulation. We used EEG/ERP recording combined with (i) neuronavigated repetitive transcranial magnetic stimulation (rTMS) and (ii) concealed information detection test. An opportunistically recruited volunteer group of normal adults formed our experimental group. Results: We show that offline rTMS to dorsolateral prefrontal cortex attenuated relative P300 amplitude in response to the critical items compared to the neutral items. Conclusion: Noninvasive prefrontal cortex excitability disruption by rTMS can be used to manipulate the sensitivity of ERP signatures of deception to critical items in a concealment‐based variant of lie detection test. Abstract : Event‐related potential component, P300, is widely considered as the main EEG recorded signature associated with deception: when people deceive, P300 amplitude relatively increases in response to a critical stimulus item (e.g., the name or picture of a stolen merchandise). For the first time, we show that repetitive transcranial magnetic stimulation targeted at the dorsolateral prefrontal cortex effectively eliminates this critical difference in the P300 amplitude. Thus, magnetic stimulation of the brain can be used in order to desensitize a subject to critical stimuli in the context of lie detection.